2003
DOI: 10.1042/cs1040211
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Type II diabetes and the β2 adrenoceptor gene Gln27Glu polymorphism in the Tongan population

Abstract: As there is a high prevalence of obesity in Tonga, we aimed to determine the distribution of the beta2 adrenoceptor gene Gln(27)Glu polymorphism and to assess its relevance to obesity and to Type II diabetes, known to be prevalent in that population. A random sample of 1022 individuals from Tonga were genotyped for the Gln(27)Glu polymorphism in the beta 2 adrenoceptor gene. To assess the prevalence of obesity we measured body-mass index (BMI), fat-free mass, percentage fat and waist-to-hip ratio (WHR). To ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…• whites (all Europeans (6,8,9,10,12,14,16,18,(19)(20)(21)(22)(23)(24)(25) and the Anglo-Celtic Australian whites (7)). • Asians, Pacific Islanders, and American Indians (Japanese (4,5,11,26,27), Taiwanese Chinese (28), Koreans (29), Tongans (30), and Aymara American Indians (31)). • Americans (mixed races (13,32,33) from United States and Canada).…”
Section: Methods and Procedures The Rs1042714 (Glu27gln) Polymorphismmentioning
confidence: 99%
“…• whites (all Europeans (6,8,9,10,12,14,16,18,(19)(20)(21)(22)(23)(24)(25) and the Anglo-Celtic Australian whites (7)). • Asians, Pacific Islanders, and American Indians (Japanese (4,5,11,26,27), Taiwanese Chinese (28), Koreans (29), Tongans (30), and Aymara American Indians (31)). • Americans (mixed races (13,32,33) from United States and Canada).…”
Section: Methods and Procedures The Rs1042714 (Glu27gln) Polymorphismmentioning
confidence: 99%
“…10, 11 A meta-analysis for Arg16Gly and Gln27Glu showed that the 27Glu allele was a significant risk factor for obesity in Asians, Pacific Islanders, and Native Americans. 12 However, in the original study of the Tongan population (ie, Pacific Islanders) referred by the meta-analysis, 27Glu tended to be associated with obesity, but the association was not statistically significant, 13 implying questionable association in Oceanic populations. It is also the fact that few Oceanic populations have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Eight predominant themes classified under two key categories 28 of 'barrier' or 'benefit' to netball physical activity behavioural change were identified from the SSIs and FGDs. Themes emerging from the synthesis of stakeholder qualitative data were: (1) cultural issues; (2) gender discrimination; (3) socioeconomic factors; (4) domestic violence; (5) infrastructure issues; (6) training and/or capacity building issues; (7) human resource limitations; and (8) multisectoralism. Additional themes emerging from the barrier analysis of beneficiary groups included a lack of knowledge about the international seven-aside rules and more personalised accounts of jealousy, domestic violence perpetrated by partners and participant and partner substance use.…”
Section: Resultsmentioning
confidence: 99%
“…5 Tonga is among the top five countries in the world in terms of obesity, 6 with 84% of Tongan men and 93% of Tongan women classified as overweight or obese. 7 Trends in relation to youth are also alarming, with a study of [11][12][13][14][15][16] year olds finding that 36% of boys and 54% of girls were overweight or obese when examined against international standards. 8 As a result of these lifestyle factors, the incidence of associated chronic diseases, such as diabetes and hypertension, is increasing.…”
Section: Introductionmentioning
confidence: 99%